2002
DOI: 10.1034/j.1600-0404.2002.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

White matter changes in normal pressure hydrocephalus and Binswanger disease: specificity, predictive value and correlations to axonal degeneration and demyelination

Abstract: In spite of a refined quantification method, NPH and BD patients exhibited similar MRI changes. MRI had a predictive value in NPH patients. DWMH might relate to demyelination and PVH to neuronal axonal dysfunction. NPH and BD share the major part of symptoms and MRI changes, indicating a common pathophysiological pattern, and we raise the question of how to treat BD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 33 publications
5
83
0
2
Order By: Relevance
“…WMLs were also found to be associated with cortical atrophy and cortical hypometabolism in both dementia patients and normal elderly (24,46,47). The regional cerebral blood volume (rCBV) was also correlated with the volume of WMLs in the same lobe.…”
Section: Histopathologic Correlatesmentioning
confidence: 93%
See 2 more Smart Citations
“…WMLs were also found to be associated with cortical atrophy and cortical hypometabolism in both dementia patients and normal elderly (24,46,47). The regional cerebral blood volume (rCBV) was also correlated with the volume of WMLs in the same lobe.…”
Section: Histopathologic Correlatesmentioning
confidence: 93%
“…The disruption of subcorticalcortical connections by WMLs may be detrimental to cortical gray matter integrity and result in cognitive and emotional dysfunctions. Although executive function can be impaired by WMLs regardless to their locations due to substantial convergence of fiber pathways on the frontal lobes (24), neurobehavioral conditions associated with WMLs were not uniform by the location of WMLs. The risk of dementia (15,20) and severity of cognitive impairment in demented patients (34) were preferentially associated with PVWML rather than DWML.…”
Section: Functional Correlatesmentioning
confidence: 95%
See 1 more Smart Citation
“…[28][29][30] Furthermore, postoperative reduction of WMLs in iNPH correlates with clinical improvement. 31,32 It is thus possible that clinical improvement after shunt surgery is attributable to reversal of white matter changes.…”
mentioning
confidence: 99%
“…It has been shown that shunt surgery improves symptoms in those with coexisting iNPH and dementia due to extensive white matter disease, 39 and white matter changes are reduced following CSF drainage. 31,32,39 Another main limitation was the use of CT. WMLs are better visualized with MRI and were rated in a rather crude way. Several of the CT scans were made using imaging techniques that are inferior to modern standards and we were thus unable to quantify volume of WMLs or analyze blood flow.…”
mentioning
confidence: 99%